Natures Uorden - Sønderby Jepsen, Christian (Denmark, 2015)
Naturens Uorden (Natural Disorder) is a documentary about Jacob Nossell-a journalist and comedian who suffers cerebral palsy. The film documents Jacob's process of setting up a self-reflecting, autobiographic play on the Danish Royal Theatre and expands into the scientific world of modern ethical questions regarding eugenics and Jacob's right to life.
Verzio Film Festival Submission
Keywords: Documentary films